(untitled) (Research, Society and Development, 2021)
The present study aims to conduct a literature survey about the quality of life of patients with diabetes mellitus in primary care. This is an integrative literature review, which searched the Virtual Health Library (VHL), with the help of the databases Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), Nursing Database (BDENF) and PUBMED. The articles were collected from January to February 2021. The following descriptors were used: Primary health care, Diabetes mellitus, Health education, Health promotion, and Quality of life. After applying the inclusion criteria, 25 studies remained. Several means are used to reduce serious complications to patients with diabetes, such as drug treatment, physical activity, and other means that can make this patient have a good quality of life that does not affect so much his routine.